2016
DOI: 10.1111/cob.12140
|View full text |Cite
|
Sign up to set email alerts
|

Treatment satisfaction with different weight loss methods among respondents with obesity

Abstract: Satisfaction with weight loss (WL) methods has been correlated with the effectiveness, long-term compliance and commitment to weight management. This study explored treatment satisfaction associated with different WL methods among patients with obesity. Cross-sectional data were analysed from the 2012 US National Health and Wellness Survey. Respondents with obesity were categorized as having a WL procedure (e.g., gastric bypass and gastric banding) or using a prescription medication for WL (Sur/Rx), vs. using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…These Portion‐Control Strategies Trial findings also parallel more general findings for the effects of satisfaction on weight loss. Previous studies have found that initial satisfaction with the type of intervention predicted subsequent weight loss and that overall satisfaction with initial weight loss predicted long‐term weight loss and maintenance . Satisfaction with a prescribed diet may affect the likelihood of adopting and maintaining dietary changes and thus could have a substantial impact on weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…These Portion‐Control Strategies Trial findings also parallel more general findings for the effects of satisfaction on weight loss. Previous studies have found that initial satisfaction with the type of intervention predicted subsequent weight loss and that overall satisfaction with initial weight loss predicted long‐term weight loss and maintenance . Satisfaction with a prescribed diet may affect the likelihood of adopting and maintaining dietary changes and thus could have a substantial impact on weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy was also advocated in recent guidelines from both the American Diabetes Association and the American Association of Clinical Endocrinologists guideline on the management of type 2 diabetes mellitus . Research has also suggested that satisfaction with weight loss may be higher when weight‐loss medications are used compared with lifestyle approaches, including dietary modification, exercise, and use of weight‐loss supplements, and that use of a weight‐loss medication is associated with greater weight loss .…”
Section: Introductionmentioning
confidence: 99%
“…For example, validated questionnaires have shown the impact of obesity on quality of life as well as the improvements that result from weight loss . Additionally, satisfaction with the type of intervention and with the initial amount of weight loss have been shown to predict long‐term weight loss. These broad measures would be supported by administering a more specific questionnaire related to diet satisfaction, such as the DSat‐45.…”
Section: Introductionmentioning
confidence: 99%